Prevalence of postpartum depression in Nuuk, Greenland – a cross-sectional study using Edinburgh Postnatal Depression Scale - Motzfeldt, Iben (Co-Action Publishing, 2013)
OBJECTIVE: The aim of this study is to estimate the prevalence of postnatal depression in Nuuk, Greenland. STUDY DESIGN: Cross-sectional study. METHODS: The primary health care system in Nuuk initiated a project aiming to screen new mothers for depression using the Edinburgh Postnatal Depression Scale (EPDS). EPDS has a range on a scale from 0 to 30. All mothers residing in Nuuk who had given birth in 2011 were included in the study group. The screening was performed by health care visitors approximately 3 months following birth. Mothers who scored 13 points or above were defined as having possible postpartum depression (PPD). These mothers were then referred to a physician. A score at or less than 8 was defined as normal, whereas an intermediate score from 9 to 12 indicated a need for an extra visit. RESULTS: During 2011, a total of 217 mothers gave birth in Nuuk. Of them, 80.2% (174) were screened for PPD using EPDS. Fifteen mothers scored 13 points or above corresponding to a prevalence of possible PPD at 8.6% (15/174). Seventy-nine percentage scored less than 9 points (137/174), whereas 15% (22/174) scored from 9 to 12 points. CONCLUSION: PPD seems to be a common problem in Nuuk, Greenland. EPDS seems to be a valuable tool in identifying women with PPD and vulnerable mothers with extra needs for support in a Greenlandic context. Continual routine screening is recommended.